Misfire : inside the downfall of the NRA - Mak, Tim (Dutton, an imprint of Penguin Random House LLC, 2021)
"A blistering exposé of the National Rifle Association, revealing its people, power, corruption, and ongoing downfall, from acclaimed NPR investigative reporter Tim Mak"--